"From PI to IP": Litigation Response to Tort Reform. (26th March 2018) - Avraham, Ronen; Golden, John M.
Abstract: For helpful comments and input, the authors thank David Abrams, Alma Cohen, Allan Ferrel, Michael Frakes, Mark Lemley, Jonathan Masur, Michael Meurer, Michael Risch, Pam Samuelson, David Schwartz, Ted Sichelman, Charles Silver, Matthew Spitzer, Melissa Wasserman, Heidi Williams, prior anonymous reviewers, and participants in the 2012 Empirical Patent Law Conference sponsored by Cornell Law School and the University of Illinois College of Law, the 2012 Intellectual Property Scholars Conference, the University of Texas School of Law's Drawing Board workshop, a conference in memory of Ted Eisenberg (Tel Aviv Univ, 2015), and Empirical Legal Studies Workshop (Tel Aviv Univ, 2015). The authors thank Melissa Bernstein, Ross MacDonald, Grace Matthews, and Jane O'Connell for research assistance. The first part of the title is in quotation marks because it was also the first part of the title for a 2005 news story in the journal IP Law & Business (Cohen 2005 ).